An Assessment of the Investment Climate in South Africa - Clarke, George R.G.; Habyarimana, James; Ingram, Michael; Kaplan, David; Ramachandran, Vijaya (Washington, DC: World Bank, 2012)
The objective of the South Africa Investment Climate Assessment (ICA) is to evaluate the investment climate in South Africa in all its operational dimensions and to promote policies to strengthen the private sector. The investment climate is made up of the many location-specific factors that shape opportunities and incentives for firms to invest productively, create jobs, and expand. These factors include macroeconomic and regulatory policies, the security of property rights and the rule of law, and the quality of supporting institutions such as physical and financial infrastructure. The main source of information for the ICA is a survey of over 800 formal private enterprises. The survey includes data on firm productivity, the cost of doing business, the regulatory environment, the labor market, the financial sector, the trade regime, and levels of investment. The analysis links business environment constraints to firm-level costs and productivity. Also, the investment climate and performance of firms in South Africa can be compared with those of firms in the more than 70 low- and middle income countries in which Investment Climate Surveys (ICSs) have been conducted.